A dark yellow fluorescent protein (YFP)-based Resonance Energy-Accepting Chromoprotein (REACh) for Forster resonance energy transfer with GFP. - Ganesan, S; Ameer-Beg, S; Ng, T; Vojnovic, B; Wouters, F (2006)
Förster resonance energy transfer (FRET) microscopy is a powerful technique that enables the visualization of signaling intermediates, protein interactions, and protein conformational and biochemical status. With the availability of an ever-increasing collection of fluorescent proteins, pairs of spectrally different variants have been used for the study of FRET in living cells. However, suitable spectral overlap, necessary for efficient FRET, is limited by the requirement for proper emission separation. Currently used FRET pairs represent compromises between these opposing spectral demands that reduce the maximally attainable FRET sensitivity. We present a previously undescribed FRET acceptor, a nonfluorescent yellow fluorescent protein (YFP) mutant called REACh (for Resonance Energy-Accepting Chromoprotein). REACh allows the use of the photophysically superior FRET donor EGFP, with which it exhibits optimal spectral overlap, which obviates the need for narrow spectral filtering and allows additional fluorescent labels to be used within the same cell. The latter allows the generation of sophisticated bioassays for complex biological questions. We show that this dark acceptor is ideally suited for donor fluorescence lifetime imaging microscopy (FLIM) and confirm these measurements with an independent intensity-based donor fluorescence quenching resonance energy transfer (FqRET) assay. REACh also can be used in donor photobleaching kinetics-based FRET studies. By detecting FRET between a GFP-tagged ubiquitination substrate and REACh-labeled ubiquitin, we imaged the active ubiquitination machinery inside cells. This assay therefore can be used to study proteins whose function is regulated by ubiquitination.